Studies on the fauna of Curacao and other Caribbean islands - Hummelinck, P.W.; Van der Steen, L.J. (Utrecht Foundation for scientific research in Surinam and the Netherlands, 1979)
contents: W.P. Nagelkerken. Biology of the graysby, Epinephelus cruentatus, of the coral reef of Curaçao
Keywords: Zoology--Carribean area; Zoology--Netherlands Antilles; Zoology--Curacao.